Analisis Kinetika Pertumbuhan Mikroalga Spirulina Sp. Menggunakan Pemodelan Richard dan Gompertz pada Fotobioreaktor Algaetree - Setiantoro, Arief Eko; Dewayanto, Nugroho; Budiman, Arief (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Algaetree is a closed cultivation system with a photobioreactor type created by Gadjah Mada University in collaboration with the Indonesian Institute of Arts Yogyakarta. The aim of this research was to see the effectiveness of the growth kinetics of the microalgae type Spirulina sp. The research was carried out by carrying out variations in data sampling at 3 (three) points where microalgae grow in Algaetree. The dose was 10 ml using the sampling method, then 2 ml was taken to be examined using a microscope and the number of microalgae cells found on the haemocytometer was counted. The microalgae cells were studied and counted on 4 haemocytometer columns, then the number of cells was accumulated and the standard deviation and growth kinetics were calculated using Microsoft Excel and Python software. As a result, it was found that the highest cell number of microalgae on the Algaetree was 69166.67 cells/ml, with a standard deviation of 4249.18, while the maximum growth kinetics of microalgae on the Algaetree with the Richard model and the Gompertz model, the most significant value was the Richard model, namely (miumax ) 1.9958, curve fitting parameter (A) 6.8700, stationary phase (V) 397.43, and r-square (R^2) close to 1, namely 0.9674. This value shows that there is a match between the data processed and the cultivation system used. The results of the cultivation process can be seen that the kinetics of microalgae growth is quite significant, meaning that spirulina type microalgae can grow well in a tool called Algaetree. In the next process, Algaetree can be used as a reference object for comparing microalgae growth from a closed cultivation system with an open cultivation system.